Utilization of Shell Waste as Organic Fertilizer in Gending, Probolinggo Regency - Ulva K.D, Nourma; Nadilah Iskina Maulaya; Ummu Athiyyah Ismatul Maula (Khidmatuna (Jurnal Pengabdian Kepada Masyarakat), 2023)
Curahsawo Village, located in Gending Subdistrict, Probolinggo Regency, is famous for its marine products, making it one of the areas producing shellfish, especially mussels. In addition to providing economic value, the clam industry also produces waste in the form of discarded shells. The accumulation of shell waste in residential areas has become an environmental problem and impacted the local landscape. Although some shells are used for crafts, the demand is low. As a result, the accumulation of shell waste has increased, posing a threat to the environment. To address this issue, the implementation of the KKN program, Pancamarga University students will take a participatory approach by actively involving the Curahsawo Village community in every stage of the program. The first step will involve counseling on the importance of waste management and the benefits of clam shells as organic fertilizer. This program will not only raise community awareness about the environment but also help reduce the adverse impact of clam shell waste on the surrounding environment. In addition, making clam shell POC is relatively easy and does not require much cost. The production of this organic fertilizer is relatively simple, the raw materials needed for its production are quite easy to obtain, and the production cost is relatively cheap.